Circle of culture in supporting the identity process of adolescents: an action research - Maria Aparecida Bonelli; Gabriele Petruccelli; Luan Sudário Melo; Mariana da Silva Bueno San Felice; Diene Monique Carlos; Monika Wernet (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To report and discuss the experience of the Circle of Culture in a school space, with attention to the social identity of adolescents. Method: Action research, conducted under the assumptions of the Circle of Culture, from August to December 2019. Participants were 16 adolescents, enrolled in Elementary School, in a state public school, in the rural district of a city of São Paulo. Data collection took place through photographic records, participant observation and field diary. Results: The relations of friendship were the central agenda of the Circles of Culture when dialogues about their structuring and influence on the identity construction were developed. Conclusion: Circles of Culture mediated by health professionals in the school setting have the power to problematize the reality of each adolescent's life and, simultaneously, dialogue about the common, an aspect that empowers identity projects.